Defining the spectrum, treatment and outcome of patients with genetically confirmed Gorlin syndrome from the HIT-MED cohort - Kloth-Stachnau, Katja; Obrecht, Denise; Sturm, Dominik; Pietsch, Torsten; Warmuth-Metz, Monika; Bison, Brigitte; Mynarek, Martin; Rutkowski, Stefan (Frontiers in oncology, 2021)
Gorlin syndrome is a genetic condition associated with the occurrence of SHH activated medulloblastoma, basal cell carcinoma, macrocephaly and other congenital anomalies. It is caused by heterozygous pathogenic variants in PTCH1 or SUFU. In this study we included 16 patients from the HIT2000, HIT2000interim, I-HIT-MED, observation registry and older registries such as HIT-SKK87, HIT-SKK92 (1987 - 2020) with genetically confirmed Gorlin syndrome, harboring 10 PTCH1 and 6 SUFU mutations. Nine patients presented with desmoplastic medulloblastomas (DMB), 6 with medulloblastomas with extensive nodularity (MBEN) and one patient with classic medulloblastoma (CMB); all tumors affected the cerebellum, vermis or the fourth ventricle. SHH activation was present in all investigated tumors (14/16); DNA methylation analysis (when available) classified 3 tumors as iSHH-I and 4 tumors as iSHH-II. Age at diagnosis ranged from 0.65 to 3.41 years. All but one patient received chemotherapy according to the HIT-SKK protocol. Ten patients were in complete remission after completion of primary therapy; four subsequently presented with PD. No patient received radiotherapy during initial treatment. Five patients acquired additional neoplasms, namely basal cell carcinomas, odontogenic tumors, ovarian fibromas and meningioma. Developmental delay was documented in 5/16 patients. Overall survival (OS) and progression-free survival (PFS) between patients with PTCH1 or SUFU mutations did not differ statistically (10y-OS 90% vs. 100%, p=0.414; 5y-PFS 88.9% ± 10.5% vs. 41.7% ± 22.2%, p=0.139). Comparing the Gorlin patients to all young, SHH activated MBs in the registries (10y-OS 93.3% ± 6.4% vs. 92.5% ± 3.3%, p=0.738; 10y-PFS 64.9%+-16.7% vs. 83.8%+-4.5%, p=0.228) as well as comparing Gorlin M0 SKK-treated patients to all young, SHH activated, M0, SKK-treated MBs in the HIT-MED database did not reveal significantly different clinical outcomes (10y-OS 88.9% ± 10.5% vs. 88% ± 4%, p=0.812; 5y-PFS 87.5% ± 11.7% vs. 77.7% ± 5.1%, p=0.746). Gorlin syndrome should be considered in young children with SHH activated medulloblastoma, especially DMB and MBEN but cannot be ruled out for CMB. Survival did not differ to patients with SHH-activated medulloblastoma with unknown germline status or between PTCH1 and SUFU mutated patients. Additional neoplasms, especially basal cell carcinomas, need to be expected and screened for. Genetic counselling should be provided for families with young medulloblastoma patients with SHH activation.
Gesehen am 19.01.2022